Associations of residential greenspace exposure and fetal growth across four areas in Spain. (November 2022) - Torres Toda, Maria; Estarlich, Marisa; Ballester, Ferran; De Castro, Montserrat; Fernández-Somoano, Ana; Ibarluzea, Jesús; Iñiguez, Carmen; Lertxundi, Aitana; Subiza-Perez, Mikel; Sunyer, Jordi; Tardón, Adonina; Foraster, Maria; et al.
Abstract: An accumulating body of evidence has associated exposure to greenspace with improved birth outcomes, including higher birth weight and lower risk of low birth weight; however, evidence on such association with in-utero fetal growth is scarce. We explored the influence of maternal exposure to residential greenspace and fetal growth in four INMA (Infancia y Medio Ambiente) Spanish birth cohorts (2003–2008), with 2, 465 participants. Residential greenspace was characterised by the Normalised Difference Vegetation Index (NDVI) average across 100 m, 300 m, and 500 m buffers around the residence. Repeated ultrasound measurements of the abdominal circumference (AC), biparietal diameter (BPD), femur length (FL), and estimated fetal weight (EFW) were used. We created customised-generalised least squares models to evaluate associations of residential greenspace exposure on each fetal growth parameter, controlled for the relevant confounders. There were associations between the 500 m buffer and BPD, FL, and AC. We also found associations in the 300 m buffer and FL and AC. The associations in the 100 m buffer were null. Estimates were higher among participants with lower socioeconomic status. Mediation analyses found that air pollution might explain 15–37% of our associations. Mediation by physical activity was not observed. Greenspace exposure may be beneficial for fetal growth. Highlights: Repeated data on ultrasound parameters were analysed in four Spanish birth cohorts. More greenspace exposure at home in larger buffers may be beneficial for fetal growth.